An air-breathing microfluidic formic acid fuel cell with a porous planar anode : experimental and numerical investigations - Shaegh, Seyed Ali Mousavi (2012)
This paper reports the fabrication, characterization and numerical simulation of an air-breathing membraneless laminar flow-based fuel cell with carbon-fiber-based paper as an anode. The fuel cell uses 1 M formic acid as the fuel. Parameters from experimental results were used to establish a three-dimensional numerical model with COMSOL Multiphysics. The simulation predicts the mass transport and electrochemical reactions of the tested fuel cell using the same geometry and operating conditions. Simulation results predict that the oxygen concentration over an air-breathing cathode is almost constant for different flow rates of the fuel and electrolyte. In contrast, the growth of a depletion boundary layer of the fuel over the anode can be the major reason for low current density and low fuel utilization. At a low flow rate of 10 µl min−1, simulation results show a severe fuel diffusion to the cathode side, which is the main reason for the degradation of the open-circuit potential from 0.78 V at 500 µl min−1 to 0.58 V at 10 µl min−1 as observed in experiments. Decreasing the total flow rate 50 times from 500 µl min−1 to 10 µl min−1 only reduces the maximum power density approximately two times from 7.9 to 3.9 mW cm−2, while fuel utilization increases from 1.03% to 38.9% indicating a higher fuel utilization at low flow rates. Numerical simulation can be used for further optimization, to find a compromise between power density and fuel utilization.